OPTIMAL SCHEDULING ALGORITHM FOR COAL-POWERED POWER PLANTS â CONSIDERING COAL DELIVERY CONSTRAINTS - Adjie Brotosukmono, Harso
Electricity generation in Indonesia is still dominated 43,64% by coal power plants, most of which operate on the island of Java but use coal transported from other islands. As an archipelagic country, sea condition often contribute to the non-optimal scheduling of power plant operations. Because of that, a new algorithm that consider coal delivery constraints is introduced. The algorithm optimize maintenance schedule of the power plants to coal supply that affected by sea condition. The algorithm will be implemented using PyPSA – an open source library for power system analysis based on Python programming language. When applied on IEEE 9-bus system within a year period, system with newly added algorithm provides 6,29% cheaper generation cost and more optimal coal power plants utilization.